Reading Attitudes and Competence of Grade 10 Students in the Age of Social Media Microtexts - Hisola, Mary Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between exposure to social media microtexts, reading attitudes, and reading competence among Grade 10 students in the Mobo North District, Division of Masbate Province. The study was anchored on the Limited Capacity for Mediated Message Processing Theory, Schema Theory and Constructivism, and Connectivism, which explain the cognitive, developmental, and social dimensions of reading in digital environments. A quantitative descriptive-correlational research design was employed involving 127 Grade 10 students selected through stratified random sampling from a population of 189 learners. Data were gathered using an adapted questionnaire to assess students' exposure to social media microtexts and reading attitudes, while reading competence was measured using the Philippine Informal Reading Inventory (Phil-IRI). Descriptive statistics, weighted mean, Chi-square test, Pearson's product-moment correlation coefficient, Spearman's rank-order correlation, and standard deviation were used to analyze the data. The findings revealed that students were frequently exposed to social media microtexts and generally demonstrated positive reading attitudes; however, most remained at the instructional and frustration levels of reading competence. The results further showed no significant relationship between daily time spent on social media and reading competence, as well as between frequency of exposure to social media microtexts and reading competence. Conversely, a significant positive relationship was found between frequency of exposure to social media microtexts and reading attitudes. The study concludes that while social media microtexts encourage positive reading attitudes, they do not necessarily enhance reading competence. It recommends strengthening guided reading, vocabulary development, comprehension strategies, and the purposeful integration of digital literacy into classroom instruction. The study supports Sustainable Development Goal (SDG) 4 – Quality Education by providing evidence to improve literacy instruction and SDG 9 – Industry, Innovation and Infrastructure by promoting the responsible integration of digital technologies into learning. Its findings contribute to educational and digital sustainability by informing evidence-based reading interventions and supporting collaborative efforts to improve students' literacy development.
Keywords: Connectivism; Grade 10 Students; Philippine Informal Reading Inventory (Phil-IRI); Reading Attitudes; Reading Competence; Schema Theory; Social Media Microtexts; Students' Exposure to Social Media Microtexts